Ultrafast laser volume nanostructuring; a limitless perspective - Stoian, Razvan (Advanced Optical Technologies, 2023)
Ultrafast lasers are now unanimously recognized as processing tools capable of providing utmost precision. This becomes key in the context of material processing as precise feature scales can render a range of new characteristics to the processed materials. These features redesign their properties optically, mechanically, electrically, or from a chemical point of view. Precision is often accompanied by an increase in resolution. The advances in optical beam engineering and irradiation strategies, alongside with controlled material responses, have put in sight the opportunity to reach record small feature sizes, below 100 nm. Is there an intrinsic limit to optical fabrication? What are the new opportunities provided by laser processing on these scales? How one can make light adapt to matter and at the same time control the matter’s response under light on the smallest scales? In this article I intend to provide a brief overview into the latest developments in ultrafast laser volume nanostructuring, fundamentals and applications alike, stressing out the prospective roadmap and the new potential emerging from super-resolved ultrafast smart laser processing technologies.